1991
DOI: 10.1093/ije/20.2.448
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ‘Spot’ Measurements in Epidemiological Studies of the Health Effects of Magnetic Field Exposure

Abstract: In several countries, epidemiological studies are being planned, or are in progress, to test the hypothesis that a causal relation exists between exposure to extremely low frequency magnetic fields and cancer incidence. One of the major difficulties in these studies is the development of valid and efficient protocols to assess magnetic field exposure. In studies focusing on residential magnetic fields, many researchers are turning to recently developed stationary automated magnetic field monitors to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Personal exposure measures are expensive and, if the etiologically relevant period is years before the adverse effect, often impossible. Proxy measures based on known determinants of personal exposure are often available, but although the reliability of spot vs. continuous area magnetic ®eld measurement has been examined [Delpizzo, 1991], as has the association between wire code and 24 h bedroom measurement [Tarone et al, 1998], the relative or absolute validity of each is little known. There have been two previous studies examining the relationship between spot area measurements and/or 24 h measurements and personal exposure measurements, but both were based on relatively small numbers Friedman et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Personal exposure measures are expensive and, if the etiologically relevant period is years before the adverse effect, often impossible. Proxy measures based on known determinants of personal exposure are often available, but although the reliability of spot vs. continuous area magnetic ®eld measurement has been examined [Delpizzo, 1991], as has the association between wire code and 24 h bedroom measurement [Tarone et al, 1998], the relative or absolute validity of each is little known. There have been two previous studies examining the relationship between spot area measurements and/or 24 h measurements and personal exposure measurements, but both were based on relatively small numbers Friedman et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Results on the validity of short-term measurements for estimating long-term time-average exposure have been published (Delpizzo et al, 1991;London et al, 1991;Delpizzo and Salzberg, 1992;Yost et al, 1992;Kaune and Zaffanella, 1994;Schuz et al, 2000, but not much is known about the usability of short-term measurements for estimating other exposure metrics. It has been shown that residential point-intime ''spot'' measurements can be used to estimate (in addition to time-average MF) time spent above an MF threshold (Juutilainen et al, 1996;Eskelinen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This study was designed as a``validity study'' [Armstrong et al, 1995] to evaluate the quality of exposure assessment of a study on maternal exposure to residential 50 Hz magnetic ®eld (MF), conception delay and birth weight, which used spot measurements for exposure assessment. Results on the validity of spot measurements have been published [Delpizzo et al, 1991;London et al, 1991;Delpizzo and Salzberg, 1992;Yost et al, 1992;Kaune and Zaffanella, 1994;Auvinen et al, 2000;Schuz et al, 2000], but there is limited understanding of the applicability of the results in different areas with varying electric wiring practices and climates.…”
Section: Introductionmentioning
confidence: 99%